Antibiotic Bactericidal Activity Is Countered by Maintaining pH Homeostasis in Mycobacterium smegmatis - I. L. Bartek (American Society for Microbiology, 2016)
ABSTRACT Antibiotics target specific biosynthetic processes essential for bacterial growth. It is intriguing that several commonalities connect the bactericidal activity of seemingly disparate antibiotics, such as the numerous conditions that confer broad-spectrum antibiotic tolerance. Whether antibiotics kill in a manner unique to their specific targets or by a universal mechanism is a critical and contested subject. Herein, we demonstrate that the bactericidal activity of diverse antibiotics against Mycobacterium smegmatis and four evolutionarily divergent bacterial pathogens was blocked by conditions that worked to maintain intracellular pH homeostasis. Single-cell pH analysis demonstrated that antibiotics increased the cytosolic pH of M. smegmatis, while conditions that promoted proton entry into the cytosol prevented intracellular alkalization and antibiotic killing. These findings led to a hypothesis that posits antibiotic lethality occurs when antibiotics obstruct ATP-consuming biosynthetic processes while metabolically driven proton efflux is sustained despite the loss of proton influx via ATP synthase. Consequently, without a concomitant reduction in respiratory proton efflux, cell death occurs due to intracellular alkalization. Our findings indicate the effects of antibiotics on pH homeostasis should be considered a potential mechanism contributing to antibiotic lethality. IMPORTANCE Since the discovery of antibiotics, mortality due to bacterial infection has decreased dramatically. However, infections from difficult to treat bacteria such as Mycobacterium tuberculosis and multidrug-resistant pathogens have been on the rise. An understanding of the cascade of events that leads to cell death downstream of specific drug-target interactions is not well understood. We have discovered that killing by several classes of antibiotics was stopped by maintaining pH balance within the bacterial cell, consistent with a shared mechanism of antibiotic killing. Our findings suggest a mechanism of antibiotic killing that stems from the antibiotic’s ability to increase the pH within bacterial cells by disrupting proton entry without affecting proton pumping out of cells. Knowledge of the core mechanism necessary for antibiotic killing could have a significant impact on the development of new lethal antibiotics and for the treatment of recalcitrant and drug-resistant pathogens.